Pemberdayaan Masyarakat Terhadap Pengelolaan Dana Desa - Syahruddin Syahruddin; Fransin Kontu; Hesty Tambajong; Aenal Fuad Adam (SOCIETAS, 2023)
Realizing people's welfare is one of the goals of national development. The Birth Law of the Republic of Indonesia No. 6 of 2014 concerning Villages provides new opportunities for village communities to develop their capacities and abilities as subjects of development, and one of the elements that helps improve the standard of living of village communities is the provision of village funds. The purpose of this study is to describe community empowerment in managing village funds and to analyze the factors that influence village fund management on the level of community empowerment in Erambu Village, Sota District. Purposive sampling was used to identify informants in this study, which used a qualitative descriptive methodology. The results of the study show that community empowerment in managing village funds in Erambu Village has been going well. In the planning stage, the community has participated in conveying programs, activities, and development needs that will become development priorities in village-level musrenbang activities. Furthermore, in the implementation stage, the village community also played a role; although there were still frequent miscommunications with village officials, this did not become a serious obstacle that hindered the implementation of activities. In the supervision stage, the community has also been involved, although it has not been maximized due to educational factors and public awareness of supervision over the management of village funds, which is still low. The factors that influence community empowerment in managing village funds in Erambu Village are leadership, communication, and community education.